Response of three tossa jute (Corchorus olitorius L.) cultivars produced in Benin to salinity stress at germination and young plant stages - LOKO, Belvida; GANDONOU, GBOSSÈGNON CHRISTOPHE BERNARD (My University, 2020)
The response of three tossa jute cultivars Ordinaire, 5-Doigts and Acc : Sud 2 to salt stress was evaluated at germination and young plant stages. Five NaCl concentrations: 0; 30; 60; 90 and 120 mM NaCl were used. Seeds were submitted to NaCl in petri dishes and germination was checked every day during thirty days in a completely randomized design with four replicates. Four-week old plants were submitted in pots to the same five NaCl concentrations by irrigation every two days for two weeks in screen house. NaCl reduced seed germination rate in all cultivars from day 2 to day 30 and the germination index. At the end of the 30 days, salt stress reduced the final germination percentages with a significant difference among cultivars: cultivar 5-doigts was the least affected than the two other cultivars. Salt effect caused a reduction of young plant growth whatever the growth parameter considered with a significant difference among cultivars. The growth of cultivar Acc:Sud 2 was more affected by salt stress with the lowest salt tolerance index whereas that of cultivar Ordinaire was the least affected with the highest salt tolerance index. Thus, cultivar 5-Doigts appeared as the most resistant to salt stress at germination stage among the three cultivars; whereas cultivar Ordinaire followed by 5-Doigts was the most salt resistant at young plant stage.
Keywords: Germination; Leafy vegetable; Plant growth; Salt-resistance; Tossa jute